A Study of the Deployment of Institutional Repositories in Colleges and Universities in Connecticut - Clarke, Christopher D.; Kim, Hak Joon (Practical Academic Librarianship: The International Journal of the SLA Academic Division, 2023)
In the past several years, many colleges and universities have developed institutional repositories as a means of highlighting the research and scholarship conducted at their institution as well as a means of combating the current publication model. Past studies have concentrated on growth in the total number of repositories, but none has looked at how the number of repositories in a particular region compares to those institutions without a repository. The primary purposes of this study were to find out how many colleges and universities in Connecticut have developed institutional repositories and how they have used these institutional repositories. Overall, this study revealed that less than a third of the academic institutions in Connecticut have institutional repositories. These repositories are most frequently found in the state sponsored universities and the independent, nonprofit schools. On the other hand, none of the community colleges, which constitute one of the largest proportion of schools in the state behind independent, nonprofits, has a repository. A vast majority of the repositories are registered with OpenDOAR, and nearly all of them use Digital Commons as their platform. The two most popular types of content found in Connecticut institutional repositories are journal articles and theses & dissertations.
Keywords: dept.ils; peer-reviewed; ⛔ No DOI found

Academic pursuits and involvement in decision-making: study on the formation of U.S. university think tanks - Lyu, Qing; Bielefield, Arlene; Liu, Yan Quan (Administrative Sciences, 2023)
This paper analyzes the concept of think tanks and concludes that think tanks have three basic characteristics. Firstly, they are based on academic research, relatively independent operation, and aim to serve scientific decision-making. Taking Ivy League think tanks as an example, this paper provides a preliminary discussion of ways for think tanks to maintain the scientific nature of their research, maintain the independence of their operations, and disseminate research results to enhance their influence. It covers institutional mission, research team construction, institutional governance, fundraising, achievements and activities, and alumni networks. This paper proposes a framework of university think tank generation paths associated with the essential characteristics of think tanks. The paper points out that, as a research consulting organization grown out of universities, university think tanks must maintain the scientific nature and independence of research while providing support and services for decision-making. Only in this way can they truly serve scientific and democratic decision-making, gain the trust of the public and have a real lasting influence.
Keywords: American university affiliated think tank; characteristics of think tank; decision-making; dept.ils; peer-reviewed; the ivy league university; think tank operation mechanism

Services to mobile users: the best practice from the top-visited public libraries in the US - Liu, Yan Quan; Lewis, Sarah (Information Technology and Libraries, 2023)
Libraries are adapting to the changing times by providing mobile services. One hundred fifty-one libraries were chosen based on circulation, with at least one library or library system from each state, to explore the diverse services provided to mobile users across the United States. According to the data, mobile apps, mobile reference services, mobile library catalogs, and mobile printing are among public libraries’ most-frequently offered services, as determined by mobile visits, content analysis, and librarian survey responses. Every library examined had at least one mobile website, mobile catalog, mobile app, or webpage adapted for a mobile device. Following the COVID-19 outbreak, services such as mobile renewal, subscriber database access, mobile reservations, and the ability to interact with a librarian were expanded to allow better communication with customers—all from the comfort and safety of their own homes. Libraries are continually looking for innovative methods to assist their mobile customers as the world changes.
Keywords: Mobile Apps; Mobile services; Public Libraries; SCSU-student; Survey study; dept.ils; peer-reviewed

Private post-secondary library websites and the ADA: compliancy and COVID-19 - Bielefield, Arlene; Liu, Yan Quan; Waimon, Victoria (Universal Access in the Information Society, 2023)
This study explores whether US post-secondary institutions (PPI) follow philosophies to foster inclusive communities, providing resources for those individuals with disabilities thrive socially, personally, and academically, while there have been no thorough studies conducted to determine web accessibility of the nation’s top-ranked PPI library webpages. Additionally, this study pioneers in comparison with the accessibility of PPI’s library homepages fighting COVID-19. The study evaluated the library homepages of the premium PPIs based on Money.com’s 2019 list of “The Best Colleges in America” via the WAVE web accessibility evaluation tool. The outcomes determined that most of the library homepages analyzed were littered with numerous errors, and the shift to online-based research in learning had no significant impact on the number of errors WAVE detected. The disconcerting findings of this study demonstrate the overall failure to recognize the importance of web accessibility or perhaps even the indifference toward accessibility on the part of the PPI community.
Keywords: ADA; Academic libraries; Accessibility; COVID-19; Disability; Overall failure; Philosophical aspects; Post-secondary institutions; Private colleges and universities; SCSU-student; Section 508; WAVE; WCAG; Web accessibility; Websites; dept.ils; peer-reviewed